Blood Transfusion in Obstetrics - Nigam, A; Prakash, A; Saxena, P (Kathmandu University Medical Journal, 2015)
Transfusion of blood and blood components is a common practice in obstetric wards but it is not without risk. The incidence of transfusion reactions varies from 4 in every hundred transfusions for non-haemolytic reactions to one in every 40,000 for haemolytic transfusion reactions. The physiological basis of blood transfusion is outlined in this article. Most of the donated blood is processed into components: packed red cells (PRBCs), platelets, and fresh frozen plasma (FFP) or cryoprecipitate. Various alternatives to blood transfusion exist and include autotransfusion, pre-autologous blood storage, use of oxygen carrying blood substitutes and intraoperative cell salvage. Despite the risks associated with transfusions, obstetricians are frequently too aggressive in transfusing blood and blood products to their patients. Acute blood loss in obstetrics is usually due to placenta praevia, postpartum blood loss and surgery related. An early involvement of a consultant obstetrician, anaesthetist, haematologist and the blood bank is essential. There are no established criteria for initiating red cell transfusions and the decision is purely based on clinical and haematological parameters, which have been discussed along with the general principles of blood transfusion in obstetrics and some practical guidelines. Kathmandu Univ Med J 2013; 11(4): 355-359